Review of Teenlink: A health service for children and adolescents of parents with substance use. (23rd September 2016) - Zehetner, Anthony; Iatrou, Popi; Lampropoulos, Basiliki; Phillips, Natalie
Abstract : Aim: To evaluate Teenlink, a wide‐ranging medical and psychological health service addressing the needs of children and adolescents in substance‐using families, who are at increased risk of developmental and psychosocial problems. Methods: Retrospective record review of 124 children, from 92 families seen over a 13 year period. Results: Polysubstance use and mental illness were common amongst parents. Children often presented with emotional and behavioural problems. Teenlink provided parenting skills, individual and family work, medical care, case management, advocacy, collaboration and education with adult drug and alcohol services. Conclusions: The chronic and complex nature of parental addiction, need for ongoing support and tailored service utilisation, reflected the length of engagement.